Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Hasil Belajar IPS Siswa Kelas VII.D SMP Negeri 12 Mataram - Muhsiniadi, Muhsiniadi (Lembaga Yasin AlSys, 2022)
The purpose of this study was to determine the increase in social studies learning outcomes through the application of the Discovery Learning method for Class VII.D students of SMP Negeri 12 Mataram in the 2021/2022 academic year. This research is a Classroom Action Research (CAR), using two cycles through the planning, action, observation, and reflection stages. As subjects in this study were class VII.D students for the 2021/2022 academic year with a total of 32 students, consisting of 17 male students and 15 female students. The results of this study indicate that of the number of students, namely 32 people in the initial conditions, students who have a good level of attention are 21 students or if the percentage is 65.63%. In the first cycle stage, there were 26 students or if the percentage was 81.25%, this proved an increase of 15.62% from the initial conditions. Then in the second cycle of students whose attention is categorized very well, there are 32 students or 100%. This proves an increase of 18.75% from cycle II. Based on the results of this study, it can be concluded that social studies learning by applying or using the Discovery Learning model can improve student learning outcomes for class VII.D SMP Negeri 12 Mataram.